Comparative Analysis of the Performances of the Turkish Super League with the 5 Biggest Football Leagues of Europe and the Parameters Affecting Performance - Erdoğan, Selçuk; Kerkez, Fatma (Progress in Nutrition, 2021)
This study aims to examine some basic football-specific variables (goals scored, attack time resulting in a goal, the average number of passes before the goal, the penalty with the goal, shot finishing a goal, total number of corner kicks, ball possession) in the leagues of the countries ranked in the top 5 in Europe according to the TSL and UEFA rankings. It is the comparative analysis by looking at the match statistics. Data of all matches played by the top 3 teams in Turkish Super Lig (TSL), Spanish La Liga (SLL), English Premier League (EPL), Italian Serie A (ISA), German Bundesliga (GB), and French Ligue 1 (FL1) in 3 seasons (2015/2016, 2016/2017, 2017/2018). It has been evaluated separately. Parameters such as pass, shooting, ball possession, defense, and attack are vital in determining the winning teams in football. It has been found that TSL teams are behind the teams in the leagues of the top five countries in Europe in realizing the basic parameters in the football game. It is thought that the inclusion of exercises for the basic parameters of football in the coaches’ training programs in the Super League teams will contribute to the development of football. In addition, it can be said that focusing more on the above-mentioned parameters while raising athletes in the infrastructure of the teams in Turkey will positively affect the development of both technical and athlete’s behaviors of football players.